Rice GROWTH-REGULATING FACTOR 7 controls tiller number by regulating strigolactone synthesis. (1st November 2020) - Chen, Yunping; Dan, Zhiwu; Li, Shaoqing
ABSTRACT: As an important transcription factor family, GROWTH-REGULATING FACTORs ( GRFs ) are involved in central development processes, including growth regulation, insect and disease resistance, and stress response. The OsGRF7 has recently been shown involving in modulating leaf angle through regulating GA and IAA metabolism. Interestingly, we found that OsGRF7 negatively regulates the tiller number. However, the detailed molecular mechanisms of OsGRF7 underlying the tiller number determination are still not understood. Here, we report that OsGRF7 directly targets the promoter of the NODULATION SIGNALING PATHWAY2 ( OsNSP2 ), a key factor involving in the strigolactone synthesis. Correspondingly, OsGRF7 alters the expression level of OsNSP2 and the endogenous strigolactone content, which rendered repression of the outgrowth of the axillary buds. These findings unveil a novel function of OsGRF7 in rice tillering determination.